ANIMASI PEMBELAJARAN SISTEM PENCERNAAN PADA MANUSIA BERBASIS MULTIMEDIA DI SD NEGERI NO 034820 LAU PETUNDAL - Sihotang, Alpredo; Jamaluddin, Jamaluddin; Lumbantoruan, Gortap (Universitas Methodist Indonesia, 2023)
The objective of this study is to create and assess an interactive educational animation about the human digestive system for elementary school students at SD Negeri No 034820 Lau Petundal. The development method uses a multimedia approach that involves designing, producing, and testing animations as learning tools.The results showed that the multimedia-based learning animation of the digestive system was able to improve students' understanding of the material. Thus, This educational animation serves as a viable alternative to effectively facilitate the learning process about the digestive system in elementary school students, contributing to the development of education that is more interesting and easy to understand.